2006
DOI: 10.1590/s1415-43662006000300007
|View full text |Cite
|
Sign up to set email alerts
|

Matéria orgânica e propriedades físicas de um Argissolo Amarelo Coeso sob sistemas de manejo com cana-de-açúcar

Abstract: RESUMOO cultivo contínuo da cana-de-açúcar por longo tempo sob diferentes manejos em solos de tabuleiros costeiros pode causar alterações na matéria orgânica e nas propriedades físicas do solo. Estudaram-se os efeitos de diferentes sistemas de manejo com cana-de-açúcar nas propriedades de um Argissolo Amarelo Coeso, na usina Triunfo, Estado de Alagoas. Os sistemas de manejo consistiram de uma área não irrigada, uma área irrigada, uma com aplicação de vinhaça e outra sob floresta nativa, sob condição original. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
33

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 16 publications
2
13
1
33
Order By: Relevance
“…These findings are completely contrary to those reported by Silva et al (2006) in an Argissolo Amarelo coeso, a common soil in coastal tableland environment. The authors reported that 25 years of cultivation with soil tillage, using disking operations in the renovation of cane fields and burning sugarcane before harvesting, caused reduction in the carbon content of POM and MOM in the layer of 0-0.2 m. These negatives effects indicate the importance of residue retention and reduction of tillage for soil carbon storage, and reinforce the importance of fractions of the organic matter to assess soil management practices.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are completely contrary to those reported by Silva et al (2006) in an Argissolo Amarelo coeso, a common soil in coastal tableland environment. The authors reported that 25 years of cultivation with soil tillage, using disking operations in the renovation of cane fields and burning sugarcane before harvesting, caused reduction in the carbon content of POM and MOM in the layer of 0-0.2 m. These negatives effects indicate the importance of residue retention and reduction of tillage for soil carbon storage, and reinforce the importance of fractions of the organic matter to assess soil management practices.…”
Section: Discussioncontrasting
confidence: 99%
“…By comparing this value with the MWD obtained in the second evaluation, it was possible to verify that Ultisol showed values higher than 0.5mm for both cultivated and fallow areas, which makes the latter be considered relatively resistant to crumbling and dispersion. Silva et al (2006) evaluated the distribution of classes of aggregates obtained by a wet processing of cohesive Ultisol cultivated with sugarcane and observed the decrease of aggregates larger diameter (> 2.00 mm and 2-1 mm) in the 0.00 to 0.20m and 0.20 to 0.40m layers. The GMD showed the highest values for fallow area, although did not differ significantly when only the soil sample depth was considered, and there was no significant interaction between sampling sites and depths (Table IV).…”
Section: Discussionmentioning
confidence: 99%
“…Those contents are common for coastal tableland soils, and may vary upwards in soils under forest (SILVA et al, 2006b) and downwards in soils under agricultural use (FERNANDES et al, 2011;PACHECO;CANTALICE, 2011). The V values in the 0-20 cm layer presented an overall average of 62%, with only the RF group presenting low content (33%).…”
Section: The Entire Datamentioning
confidence: 99%
“…The POM and DOC content also contributed to this, but to a lesser degree. In other words, if WSA variations are sensitive to use and management (VASCONCELOS et al, 2010) and they present significant and positive correlation with OC (SILVA et al, 2006b), its extreme dependence on the texture hinders the comparison of data for coastal tableland soils, so varied in texture. …”
Section: Samples From 0-5 CM Of Depthmentioning
confidence: 99%
See 1 more Smart Citation